A key role of the PGC-1α/ERR-α pathway in regulation of angiogenic factors in proliferative diabetic retinopathy - Abu El-Asrar, Ahmed M.; Nawaz, Mohd I.; Ahmad, Ajmal; Siddiquei, Mairaj M.; Allegaert, Eef; Gikandi, Priscilla W.; De Hertogh, Gert; Opdenakker, Ghislain (Frontiers in Endocrinology, 2025)
BackgroundPGC-1α is induced by hypoxia and interacts with the receptor ERR-α to stimulate angiogenic factors expression and promote angiogenesis. We investigated the possible role of the PGC-1α/ERR-α pathway in regulating angiogenic factors expression in proliferative diabetic retinopathy (PDR).MethodsWe analysed vitreous fluid samples from PDR and non-diabetic patients and epiretinal fibrovascular membranes from PDR patients. Streptozotocin-treated rats were used as a model of diabetic retinopathy. Vitreous samples, epiretinal membranes, rat retinas, human retinal Müller glial cells and human retinal microvascular endothelial cells (HRMECs) were studied by Western blot analysis, ELISA and immunohistochemistry. Levels of reactive oxygen species (ROS) were determined with spectrofluorometric analysis.ResultsImmunohistochemical analysis demonstrated co-expression of PGC-1α and ERR-α in endothelial cells and leukocytes in epiretinal membranes. Angiogenic activity, determined by the numbers of CD31-positive vessels, correlated significantly with PGC-1α and ERR-α expression levels. PGC-1α, ERR-α and the angiogenic biomarkers vascular endothelial growth (VEGF) and angiopoietin 2 were significantly increased in PDR vitreous samples. Diabetes induced upregulation of PGC-1α and ERR-α immunoreactive proteoforms in rat retinas. Cultured Müller cells and HRMECs constitutively expressed PGC-1α and ERR-α. In Müller cells, the PGC-1α inhibitor SR-18292 and the ERR-α selective inverse agonist XCT790 significantly attenuated VEGF, angiopoietin 2 and MCP-1/CCL2 upregulation induced by diabetic mimetic conditions. Treatment of Müller cells with the PGC-1α activator XLN005 induced significant upregulation of VEGF and attenuated ROS production induced by diabetic mimetic conditions.ConclusionsOur findings suggest that suppression of the PGC-1α/ERR-α pathway might impair the upregulation of angiogenic factors in PDR.